Machine Learning - Chandramouli, Subramanian; Dutt, Saikat; Dāśa, Amita (Pearson Education India, 2018)
"Table of Contents: 1 Introduction to Machine Learning 2 Preparing to Model 3 Modelling and Evaluation 4 Basics of Feature Engineering 5 Brief Overview of Probability 6 B ayesian Concept Learning 7 Super vised Learning: Classification 8 Super vised.